Training on Writing Teaching Modules for Merdeka Curriculum Based on Toba Batak Local Wisdom by Utilizing Artificial Intelligence for Teachers at SMP Negeri 2 Siborongborong - Simanungkalit, Kaleb E.; Tampubolon, Tanggapan C.; Sibarani, Sariayu; Gaol, Dinata Lumban (International Journal of Public Devotion, 2024)
Teachers at SMP Negeri 2 Siborongborong are not fully prepared for the demands of the Merdeka Curriculum, especially in terms of pedagogy, learning structure, and preparation of teaching modules. Another crucial issue is the cultural identity crisis, where many teaching modules do not integrate Toba Batak's local wisdom, causing students to lose connection with their cultural heritage. In addition, the use of technology, especially Artificial Intelligence (AI) such as Chat GPT, is still very minimal due to low technological literacy among teachers, which hinders the creation of more creative, relevant, and interactive teaching modules. This service aims to improve teacher competence in developing teaching modules using artificial intelligence (AI). The methods used include intensive training, educational technology workshops, and mentoring programs for teachers. The training results showed a significant increase in teachers' understanding of the local wisdom-based Merdeka Curriculum, with an average increase of 41% from pretest to posttest. The educational technology workshop also increased teachers' knowledge regarding using Canva and Gamma applications, with an average increase of 29%. Assessment of the teaching modules produced showed that all participants reached the minimum standard with an average score of 78, which shows the service's success in improving teacher abilities. Nevertheless, some teachers still need further assistance, especially in the aspects of learning design and evaluation.